Pelatihan Pembuatan Video Pembelajaran Berbasis Software Camtasia bagi Guru SMA Negeri 1 Dawarblandong, Mojokerto - Eko Sugandi; Nur Rohma; Anies Listyowati; Achmad Nuryadi; Cindy Asli Pravesti; Elia Firda Mufidah; Rina Asmaul; Ninik Mutianingsih; Lydia Lia Prayitno (Jurnal Pengabdian Pada Masyarakat, 2021)
CAMTASIA SOFTWARE-BASED LEARNING VIDEO MAKING TRAINING FOR TEACHERS OF SMA NEGERI 1 DAWARBLANDONG, MOJOKERTO. The Covid-19 pandemic has resulted in the use of learning media in schools to become an obstacle during the online learning process. The teachers only use existing learning media in schools and are not used to developing instructional videos. The aim of this activity is to provide training in making learning videos based on Camtasia software for 50 teachers at SMA Negeri 1 Dawarblandong, Mojokerto. The methods used in this training are discourse, discussion, mentoring, and also training to develop learning videos in accordance their fields of study. After mentoring and training in making Camtasia-based learning videos, the team of presenters and participants evaluated the learning videos that were successfully developed by the teacher. The result was that 74% of teachers at SMA Negeri 1 Dawarblandong, Mojokerto succeeded in developing interactive learning videos using Camtasia software. During the training, the participants seemed enthusiastic about taking part in the Camtasia-based learning video making training activity.